Neurogenic Bladder Management in Spinal Medula Trauma: A Literature Review - Aditya Nur Rahman; Iwan Setiawan; Dodik Nursanto; S Sulistyani (Prosiding University Research Colloquium, 2022)
Background : Neurogenic bladder is a condition in which the urinary sphincter is unable to increase or decrease its pressure in response to pressure on the bladder. This occurs due to damage to the central, peripheral, or autonomic nervous systems. Neurogenic bladder in spinal cord trauma patients is a condition that can pose a significant risk to the patient. Many medical and intervention approaches are available today. The goals of treatment for neurogenic bladder are to stop urine leakage due to overactivity of the detrusor muscle during bladder filling, to reduce intravesical pressure and vesicoureteral reflux, and to treat and prevent complications such as urinary tract infections. Purpose : Knowing the various neurogenic bladder management in spinal cord trauma patients. Method : This research is a literature review type. Literature review data was collected by browsing published articles on Pub Med, Science Direct, and Google Scholar databases. Outcome : There were 3 articles discussing the use of Clean Intermitten Catheterization (CIC), 4 articles discussing electrical stimulation, and 2 articles discussing Botox. Electrical stimulation can increase bladder capacity and suppress detrusor activity. The use of CIC makes it easier for the patient to submit urine. Botox will inhibit involuntary detrusor contractions. Conclusion : There are various treatments for neurogenic bladder in spinal cord trauma patients, such as the use of intermitten catheters, Botox injections, and electrical stimulation.